KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS TAFSIR TEMATIK: STRATEGI KOMPREHENSIF DALAM MENJAWAB PROBLEMATIKA SOSIAL KONTEMPORER - Mohammad Firmansyah; Mina Umrah Pelas; Yalizar Rahayu Sitorus; Anggreni Bako; Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the Islamic Religious Education (PAI) curriculum based on thematic interpretation as a comprehensive strategy in responding to contemporary social problems. The research method used is a literature review, which includes the collection, analysis, and synthesis of various relevant theoretical and empirical sources. The results of the study indicate that the PAI curriculum based on thematic interpretation, which integrates a deep understanding of the verses of the Qur'an with actual social issues, can improve students' competence in mastering verse interpretation and strengthen educational science competence. This study reveals that the thematic approach in learning the Qur'an makes it easier for students to understand the material. In addition, this study offers strategic steps in implementing thematic interpretation learning, which is suitable for students with a general education background. The novelty of this study lies in the combination of the concept of thematic interpretation with contemporary social problems, which have not been widely explored in the context of the PAI curriculum.